HUBUNGAN PEMBERIAN VAKSIN HAEMOPHILUS INFLUENZAE TYPE B DAN VITAMIN A DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS GELA KECAMATAN TALIABU UTARA (JURNAL KEPERAWATAN, 2015)
Abstrack: ARTI ( Acute Respiratory Tract Infection) will be occured when the immune system of the body is getting down. Some efforts could reduce the risk of ART, such as by giving Hib Vaccine and Vitamin A. The Incidence of ARTI on toddler at work area of Gela Primary Health Care Of Notrh Taliabu District in one of the most prevalent disease rather than the other disease. The aim of this research are to identify the Hib Vaccine and Vitamin A giving, also to analyze the correlation of Haemophilus Infection Type B Vaccine and Vitamin A Giving with Incidents of ARTI on Toddler. The sample in this research was taken with total sampling technique with 72 respondents as sample. The research design is using retrospective desing and the data are collected from respondents by observation sheet. The result of this research using analysis statistic Chi- Square test have gained value p= 0,001. Which is means that the value of p